(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to show the impact that the information of the supporting bodies can have and its dimensions represented by (information credibility, efficiency and effectiveness of information, cooperation with the tax administration, obligating the taxpayer, accuracy and completeness of information and the appropriate time) in tax inventory, as well as clarifying the moral differences in The response of the surveyed sample according to the personal variables represented by (gender, educational attainment, scientific specialization, job title, years of service), and the descriptive analytical approach was adopted and in light of it, the questionnaire was designed as a main tool in collecting data from the sample of (80) officials In the General Tax Authority and in the job positions represented by (assistant general manager, department manager, division official, tax examiner, auditor, others, as well as conducting personal interviews with its officials, the answers were analyzed based on the statistical program (SPSS V.18) and reached The research led to a set of conclusions, the most important of which is that there is a moral effect to remove the impact of the information of the supporting bodies, collectively and individually, in the tax inventory.